The Guardians of Nunusaku: An Eco-Theological Study of the Manusa Cosmology - Salampessy, Dastien A. J.; Hukubun, Monike; Hetharia, Henky Herzon (Program Pascasarjana UKIM, 2025)
This research aims to examine the cosmological idea of the Manusa community as “guardians of Nunusaku” in relation to ecological and theological perspectives in responding to global warming. Using a descriptive qualitative approach, this study examines the understanding and practices of the Manusa community that emphasizes the spiritual relationship between humans, nature, and God. The concept of mara’a nunue ai welu reflects the ancestral responsibility to preserve the ecosystem through traditional practices rich in spiritual and ecological values. The findings of the study indicate that the behavioral patterns of the Manusa community contribute to maintaining ecological balance through respect for nature and wise management of resources. This perspective is in line with organic theology and the concept of Imago Dei, where humans are divinely mandated to treat, not exploit, nature. Thus, an ecological understanding of humans can enrich ecological theology in fostering ethical awareness for environmental sustainability.